X-ray fluorescence analysis of the normal teeth enamel and in case of erosion (Эндодонтия Today)
In the investigation the assessment of the distribution of the elementary composition in the superficial layers of the tooth enamel in the field of erosion was held using XRF analysis. The results showed the increased content of Zn, S, Cl, K and Sr. And its maximum appeared in the middle of the erosion. Besides that in the investigation the assessment of the qualitative changes in the elementary composition of the tooth enamel in the field of erosion was held using XRF analysis. It showed that in the field of erosion the content of phosphorus decreases more intensively in comparison with calcium and, as a result, Са/Р increases.